Rogalski effect di Bursa Efek Indonesia, Bursa Efek Amerika Serikat, Bursa Efek Jerman sebelum, sesaat, dan sesudah Pandemi Covid-19 - Hanum Tanjung, Nur Azmi Aulya; Komariah, Siti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
In fact, in an efficient capital market, stock prices will experience short changes, which investors will find difficult to predict and will cause an investor to not get an abnormal return (an abnormal return). Rogalski is a negative phenomenon that usually occurs on Mondays and disappears in April. This study aims to find out how the Rogalski Effect phenomenon is on the Indonesian, United States, and German Stock Exchanges for the 2019–2021 period. In addition, to find out whether there are differences in stock returns between Mondays in January to April and other days and months, and whether there are differences in stock returns on the Indonesian, United States, and German stock exchanges during the study period, The data used is daily main stock price index data from January 2019 to December 2021. The research methods used are the comparative method and event study. While the technical analysis using normality tests, homogeneity tests, and the Independent Sample T-test The results show that there is no Rogalski Effect phenomenon in the stock exchanges of Indonesia, the United States, and Germany because there is no significant difference in the average value of stock returns between Mondays in January to April and other days and months.